Eksistensi Laboratorium Kriminal Puspomad untuk Mendukung Ketersediaan Alat Bukti Tindak Pidana di Peradilan Militer (SETARA : Jurnal Ilmu Hukum, 2022)
This study examines the institutional existence of the Criminalistics Laboratory of the Indonesian Army Military Police Center (Puspomad) and its role in supporting the availability of evidence in military criminal proceedings. Using normative juridical research supported by empirical findings, the article reviews the legal basis of military investigation and evidentiary law, including Law Number 31 of 1997 on Military Courts and internal organizational regulations of the Indonesian Army. The study finds that the existence of the Puspomad Criminalistics Laboratory has been recognized institutionally, but its operational role is still limited because supporting technical regulations, standard operating procedures, accreditation, and institutional positioning have not yet been fully strengthened. The article argues that clearer legal and organizational arrangements are needed so that criminalistics support can function effectively as a reliable evidentiary aid in military justice.